The Presupposition Analysis In “Oppenheimer” Movie : Pragmatic Study - Fabian, Muhammad Rifki; Heryono, Heri (Universitas Nahdlatul Wathan Mataram, 2024)
This study purposes to analyze the pragmatic theories of Oppenheimer movie. This research aims to conduct a pragmatic analysis of presuppositions in the film